2022
DOI: 10.1007/s10533-022-00920-0
|View full text |Cite
|
Sign up to set email alerts
|

Too much of a good thing? Inorganic nitrogen (N) inhibits moss-associated N2 fixation but organic N can promote it

Abstract: Moss-associated nitrogen (N 2 ) xation is one of the main inputs of new N in pristine ecosystems that receive low amounts of atmospheric N deposition. Previous studies have shown that N 2 xation is inhibited by inorganic N (IN) inputs, but if N 2 xation in mosses is similarly affected by organic N (ON) remains unknown. Here, we assessed N 2 xation in two dominant mosses in boreal forests (Pleurozium schreberi and Sphagnum capillifolium) in response to different levels of N, simulating realistic (up to 4 kg N h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Hence, the bacterial colonizers experience very different environmental conditions, depending on the moss host. Indeed, N 2 fixation associated with Sphagnum is less sensitive to an increase in temperature and N input compared to N 2 fixation associated with H. splendens and P. schreberi (Rousk et al ., 2015; Wang et al ., 2022). Furthermore, different bacterial communities have been found associated with Sphagnum vs other mosses (Kostka et al ., 2016; Holland‐Moritz et al ., 2021) and, thereby, N 2 fixation activity (Jean et al ., 2020; Stuart et al ., 2021).…”
Section: The Players: Biotic Controlsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the bacterial colonizers experience very different environmental conditions, depending on the moss host. Indeed, N 2 fixation associated with Sphagnum is less sensitive to an increase in temperature and N input compared to N 2 fixation associated with H. splendens and P. schreberi (Rousk et al ., 2015; Wang et al ., 2022). Furthermore, different bacterial communities have been found associated with Sphagnum vs other mosses (Kostka et al ., 2016; Holland‐Moritz et al ., 2021) and, thereby, N 2 fixation activity (Jean et al ., 2020; Stuart et al ., 2021).…”
Section: The Players: Biotic Controlsmentioning
confidence: 99%
“…Another indirect effect of climate change is increased N availability due to enhanced microbial activity in soil (Salazar et al, 2020). Nitrogen has been repeatedly shown to inhibit N 2 fixation in mossesindependent of climate changein experimental studies as well as along natural fertility gradients (Dynarski & Houlton, 2018;Zheng et al, 2019a), and this negative effect is instant (Wang et al, 2022;Figs 3b, 4). The negative effects of N additions on moss-associated N 2 fixation seems to be transient, however, and can be reversed once excess N leaves the system (Wang et al, 2022).…”
Section: Climate Changeindirect Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased N availability commonly inhibits activity of the nitrogenase enzyme (responsible for the reduction of N 2 to NH 3 ) [ 21 , 26 , 28 ]. For instance, a study investigating the effects of nutrient additions on tropical soils found that N additions caused a ~75% decrease in nitrogenase activity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen fixation activity of bacteria hosted by bryophytes is affected by abiotic factors such as temperature and moisture availability (Cusack et al, 2009; Gundale, Nilsson, et al, 2012; Permin et al, 2022; Rousk, Jones, et al, 2013), with desiccation inhibiting activity (Rousk et al, 2014). Also increased N availability can inhibit N 2 fixation in mosses (Rousk, Rousk, et al, 2013; Wang et al, 2021) and moss pH can affect N 2 fixation activity (Alvarenga & Rousk, 2021; Liu & Rousk, 2021). Furthermore, specific morphology traits linked to bryophyte hydration rate (e.g.…”
Section: Introductionmentioning
confidence: 99%